Organic electrochemical device and organic electrochemical device manufacturing method

By using a polysaccharide with a glucose-like structure and a conductive polymer, the device is fabricated more simply, addressing the fabrication challenges of non-enzymatic glucose OECT sensors and achieving effective glucose detection.

JP2025007398APending Publication Date: 2025-01-17TOHOKU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023108765
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-30
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

Non-enzymatic glucose OECT sensors face challenges in adapting to spin coating and digital printing techniques used for general device fabrication.

Method used

An organic electrochemical device is manufactured using a polysaccharide with a chemical structure similar to glucose as a sensing site, mixed with a conductive polymer, and a glycosaminoglycan, allowing for simpler fabrication by applying a channel-forming composition onto an insulating substrate with source and drain electrodes, and connecting a gate electrode via an electrolyte.

Benefits of technology

The method enables the production of an organic electrochemical device that is simpler to manufacture, with improved glucose detection capabilities, achieving a glucose detection range of 1 to 10 mM, suitable for monitoring blood sugar levels and potentially other glucose-containing solutions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025007398000007
    Figure 2025007398000007
  • Figure 2025007398000008
    Figure 2025007398000008
  • Figure 2025007398000009
    Figure 2025007398000009
Patent Text Reader

Abstract

To provide an organic electro-chemical device that enables manufacturing by a method simpler than a conventional method, and to provide a manufacturing method of the organic electro-chemical device.SOLUTION: An organic electro-chemical device comprises: a channel that includes an electric conductive polymer and glycosaminoglycan; a source electrode; a drain electrode; and a gate electrode. The glycosaminoglycan is the glycosaminoglycan composed of a repeating structure of a saccharide of at least one kind selected from a group consisting of N-acetyl-glucosamine, glucuronic acid, iduronic acid and galactose, and a disaccharide as well. The source electrode and the drain electrode are electrically connected to the channel in contact with the channel, and if an electrolyte in contact with the gate electrode and channel exists, the gate electrode is electrically connectable to the channel via the electrolyte. The electrolyte is at least one kind that is selected from a group consisting of an electrolyte solution, and an ionic liquid.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an organic electrochemical device and a method for manufacturing an organic electrochemical device. [Background technology]

[0002] In organic electrochemical sensors, glucose measuring enzymes such as glucose dehydrogenase and glucose oxidase are used to detect sugars. However, the production, storage stability and cost of the enzymes are problems.

[0003] In recent years, non-enzymatic glucose OECT sensors using organic electrochemical transistors (OECTs) that do not use enzymes have been attracting attention. The complicated device fabrication process is an issue with non-enzymatic glucose OECT sensors (Non-Patent Document 1). In previous studies, a process in which phenylboronic acid (PBA), a functional moiety that senses glucose, is embedded in the active layer by a polymerization reaction such as electrolytic polymerization, is common (Non-Patent Document 2). [Prior art documents] [Non-patent literature]

[0004] [Non-Patent Document 1] Wustoni, S., et al., “Enzyme-Free detection of Glucose with a Hybrid Conductive Gel Electrode”, Advanced Materials Interfaces, 2019, Vol. 6, 1800928 [Non-Patent Document 2] Tseng, AC, et al., “Direct Electrochemical Signaling in Organic Electrochemical Transistors Comprising High-Conductivity Double-Network Hydrogels”, ACS Applied Materials & Interfaces, 2022, Volume 14, p.24729-24740 Summary of the Invention [Problem to be solved by the invention]

[0005] However, previously reported non-enzymatic glucose OECT sensors are difficult to adapt to spin-coating and digital printing techniques commonly used for device fabrication.

[0006] An object of the present invention is to provide an organic electrochemical device that can be produced by a method simpler than conventional methods, and a method for producing an organic electrochemical device. [Means for solving the problem]

[0007] The inventors discovered that a polysaccharide having a chemical structure similar to that of glucose can be used as the glucose sensing site, instead of the conventional PBA, and that a functional membrane can be produced by simply mixing this with an active material, thereby completing the present invention. That is, the present invention includes the following aspects.

[0008] [1] A semiconductor device comprising a channel including a conductive polymer and a glycosaminoglycan, a source electrode, a drain electrode, and a gate electrode; the glycosaminoglycan is a glycosaminoglycan having a repeating structure of a disaccharide of N-acetylglucosamine and at least one sugar selected from the group consisting of glucuronic acid, iduronic acid, and galactose, the source electrode and the drain electrode are in contact with and electrically connected to the channel; If an electrolyte is present in contact with the gate electrode and the channel, the gate electrode can be electrically connected to the channel via the electrolyte, and the electrolyte is at least one selected from the group consisting of an electrolyte solution and an ionic liquid. Organic electrochemical devices. [2] The organic electrochemical device according to [1], wherein the conductive polymer is PEDOT:PSS. [3] The organic electrochemical device according to [1] or [2], wherein the glycosaminoglycan is hyaluronic acid. [4] The organic electrochemical device according to any one of [1] to [3], wherein the electrolyte is a body fluid. [5] The organic electrochemical device according to [4], wherein the body fluid is blood. [6] The organic electrochemical device according to any one of [1] to [5], which is a glucose sensor. [7] The organic electrochemical device according to any one of [1] to [3], wherein the gate electrode is electrically connected to the channel via the electrolyte solution. [8] The organic electrochemical device according to [7], which is an organic electrochemical transistor. [9] Preparing a channel-forming composition containing a conductive polymer and a glycosaminoglycan; The channel-forming composition is applied onto an insulating substrate on which a source electrode and a drain electrode are disposed, so that the channel-forming composition is in contact with the source electrode and the drain electrode to form a channel; disposing a gate electrode so as to be in electrical contact with the channel via an electrolyte; A method for manufacturing an organic electrochemical device, comprising the steps of: The glycosaminoglycan is a glycosaminoglycan having a repeating structure of a disaccharide of N-acetylglucosamine and at least one sugar selected from the group consisting of glucuronic acid, iduronic acid, and galactose. A method for manufacturing an organic electrochemical device.

[10] The method for producing an organic electrochemical device according to [9], wherein the gate electrode is disposed on the insulating substrate. Effect of the Invention

[0009] According to the present invention, it is possible to provide an organic electrochemical device that can be produced by a method simpler than conventional methods, and a method for producing an organic electrochemical device. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 is a diagram showing an embodiment of an organic electrochemical device of the present invention. [Diagram 2] FIG. 2 is a diagram showing another embodiment of the organic electrochemical device of the present invention. [Diagram 3] FIG. 3 is a schematic diagram for explaining the film forming method. [Figure 4] FIG. 4 shows a box plot of the maximum transconductance values. [Diagram 5] FIG. 5 is a plot showing the results of glucose responsiveness evaluation. [Figure 6] FIG. 6 is a semi-log plot showing the results of glucose response experiments. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, an embodiment of the present invention will be described in detail. However, the present invention is not limited to the embodiment described below, and various modifications are possible without departing from the gist of the present invention.

[0012] [Organic electrochemical devices] As shown in FIGS. 1 and 2, an organic electrochemical device 100 of the present invention comprises a channel 104 comprising a conductive polymer and a glycosaminoglycan, a source electrode 106, a drain electrode 108, and a gate electrode 102.

[0013] A source electrode 106 and a drain electrode 108 are in contact with and electrically connected to the channel 104 .

[0014] If an electrolyte 110 is present in contact with the gate electrode 106 and the channel 104 , the gate electrode 102 can be electrically connected to the channel 104 via the electrolyte 110 . 1 and 2, as an example, the source electrode 106, the drain electrode 108, and the gate electrode 106 are arranged three-dimensionally, but it is preferable to form them on the same insulating substrate 112. In that case, the channel 104 may be arranged on the source electrode 106 and the drain electrode 108, and the electrolyte 110 may be configured to be in contact with the channel 104 and the gate electrode 106 provided with a gap therebetween.

[0015] As shown in FIG. 1, the source electrode 106, the drain electrode 108 and the channel 104 are preferably disposed on an insulating substrate 112. On the other hand, it is also possible to configure the device without using the insulating substrate 112 as shown in FIG.

[0016] As the conductive polymer, PEDOT:PSS (a composite of poly(3,4-ethylenedioxythiophene) (PEDOT) and polystyrene sulfonic acid (PSS)) is preferred because it is easily available, has excellent conductivity, and is highly safe. PEDOT:PSS is usually supplied as a dispersion liquid, and can be used by diluting it appropriately with water.

[0017] The electrolyte 110 is at least one selected from the group consisting of an electrolyte solution, a gelled electrolyte solution, and an ionic liquid.

[0018] Examples of the electrolyte solution include, but are not limited to, aqueous solutions containing ionic substances such as phosphate buffered saline, and body fluids such as blood and sweat of animals, including humans. Non-limiting examples of the ionic liquid include imidazolium-based ionic liquids, pyrrolidinium-based ionic liquids, pyridinium-based ionic liquids, piperidinium-based ionic liquids, ammonium-based ionic liquids, and phosphonium-based ionic liquids. The electrolytes can be used alone or in combination of two or more.

[0019] The glycosaminoglycan is a glycosaminoglycan having a repeating disaccharide structure of N-acetylglucosamine and at least one sugar selected from the group consisting of glucuronic acid, iduronic acid, and galactose. The glycosaminoglycan is preferably at least one selected from the group consisting of hyaluronic acid and salts thereof. The molecular weight of the hyaluronic acid is not particularly limited, but in the case of sodium hyaluronate, the average molecular weight is preferably within the range of 2,827 to 4,000,000, and more preferably within the range of 1,000,000 to 2,500,000. The glycosaminoglycans can be used alone or in combination of two or more.

[0020] The organic electrochemical device of the present invention can be suitably used as a glucose sensor.

[0021] When the gate electrode is electrically connected to the channel via the electrolyte solution, the organic electrochemical device of the present invention can function and be used as an organic electrochemical transistor.

[0022] [Method of manufacturing organic electrochemical devices] The organic electrochemical device 100 of the present invention can be manufactured by preparing a channel-forming composition containing a conductive polymer and a glycosaminoglycan, applying the channel-forming composition onto an insulating substrate 112 on which a source electrode and a drain electrode are arranged so that the channel-forming composition contacts the source electrode 106 and the drain electrode 108 to form a channel 104, and arranging a gate electrode 102 so that it can be electrically connected to the channel 104 via an electrolyte 110.

[0023] The insulating substrate 112 is not particularly limited, but is preferably made of inorganic glass or a polymer such as polyethylene terephthalate or polymethacrylate.

[0024] As described above, the source electrode 106, the drain electrode 108, the gate electrode 102, and the channel 104 are preferably disposed on the same insulating substrate 112. This is because manufacturing becomes easier and is suitable for mass production.

[0025] The method for applying the channel forming composition onto the insulating substrate 112 is not particularly limited, but it is preferable to employ a digital printing technique such as spin coating or inkjet printing.

[0026] The conductive polymer and the glycosaminoglycan are as described above. EXAMPLES

[0027] The present invention will be described in more detail below with reference to experimental examples, but the present invention is not limited to the experimental examples described below.

[0028] [Experimental Example 1] A PEDOT:PSS solution was obtained by mixing 9.5mL of PEDOT:PSS (Clevios PH1000, Heraeus), 0.5mL of ethylene glycol (EG) (Fujifilm Wako Pure Chemicals), and 0.17mL of dodecylbenzenesulfonic acid (DBSA) (Kanto Chemical) (diluted 10 times) as a surfactant, and ultrasonically cleaning for 15 minutes. EG improves the crystallinity of PEDOT:PSS, thereby increasing its conductivity.

[0029] [ka]

[0030] In addition, sodium hyaluronate (Hya) (Nacalai Tesque, #18237-41) was dissolved in pure water at 0.1 wt%, and sodium chondroitin-6-sulfate (Cho) (Tokyo Chemical Industry, #C0335) was dissolved in pure water at 1.2 wt% to prepare a solution (polysaccharide solution). Note that each n in the following chemical formula independently represents a natural number.

[0031] [ka]

[0032] The PEDOT:PSS solution and the polysaccharide solution were mixed in various ratios and sonicated for 15 minutes. The viscosity of the resulting solution was measured to evaluate the solution properties.

[0033] Next, a membrane containing sodium hyaluronate (Hya) and a membrane containing sodium chondroitin-6-sulfate (Cho) as polysaccharides were prepared. First, the substrate treatment is described. The substrates used were a glass substrate, a one-side polished p-Si wafer, and a quartz substrate, and were first ultrasonically cleaned for 15 minutes each in acetone (manufactured by Nacalai Tesque), 2-propanol (IPA) (manufactured by Kanto Chemical), and pure water. In the present invention, since the crosslinking agent also has an effect on film formation, the organic electrochemical device 100 was produced by two methods, the outline of which is shown in FIG. One is a method called the substrate processing system, in which a film is formed by adding a film-forming solution to a substrate that has been treated with a crosslinking agent, and the other is a method called the crosslinking agent addition system, in which a film is formed by adding a crosslinking agent addition system to a film-forming solution to a substrate that has been treated in the normal manner. Therefore, the substrate was treated in the following two ways. The substrate treatment system involved removing any remaining organic matter by treating both sides of the substrate with ozone for 30 minutes using a UV ozone cleaner, and then performing a hydrophilic treatment. The substrate was then immersed overnight in a toluene solution containing 1 vol% of the cross-linking agent (3-glycidyloxypropyl)trimethoxysilane (GOPS) to modify the surface with GOPS. On the other hand, for the crosslinking agent-added system, only one side was subjected to hydrophilic treatment by ozone treatment for 30 minutes using a UV ozone cleaner.

[0034] [ka]

[0035] Next, the film forming method will be described. The substrate treatment system was spin-coated with the prepared polysaccharide-mixed PEDOT:PSS solution onto a GOPS-modified substrate. On the other hand, in the crosslinking agent-added system, GOPS was added as a crosslinking agent to the prepared polysaccharide-mixed PEDOT:PSS solution, and spin-coated onto a hydrophilic substrate. The spin coating conditions were 400 rpm for 10 seconds and 3000 rpm for 60 seconds. Thereafter, the substrate coated with the substrate treatment system and the crosslinking agent addition system was annealed at 130° C. for 30 minutes to obtain a spin-coated film.

[0036] The state of the substrate of each polysaccharide mixed film prepared was observed before and after immersion in pure water after annealing, and analyzed by atomic force microscopy (AFM) and UV-vis absorption spectroscopy. A single-sided polished p-Si wafer was used for AFM measurements, and a quartz substrate was used for UV-vis absorption spectroscopy. AFM measurements were performed using an atomic force microscope (AFM, SPA400, SII) in DFM mode.

[0037] <Results and Discussion> (Solution Characterization) First, we will describe the results of viscosity measurements of the polysaccharide solution. Viscosity measurements were performed by changing the mixing ratio of the polysaccharide solution to the PEDOT:PSS solution. When hyaluronic acid was dissolved in water, a small amount produced a highly viscous solution, and the viscosity increased as the ratio of hyaluronic acid to PEDOT:PSS was increased. Furthermore, the hyaluronic acid mixed solution exhibited the properties of a non-Newtonian fluid, with a large dependency on viscosity and shear rate. This is thought to be due to the acid strength of the hyaluronic acid sodium salt and PEDOT:PSS solution.

[0038] On the other hand, the viscosity of chondroitin decreased when the mixing ratio to PEDOT:PSS was increased. This is thought to be because the viscosity of the chondroitin solution is low, and the PEDOT:PSS solution was diluted by mixing. Furthermore, the chondroitin mixed solution showed no dependency of viscosity on shear rate, indicating the properties of a Newtonian fluid. The chondroitin-6-sodium sulfate used here is a sodium salt derived from sulfo groups, so it does not become liberated like hyaluronic acid, and it can be said that no particular interactions occur in the solution. From the above, it can be said that chondroitin does not have the effect of improving viscosity when mixed with PEDOT:PSS, and that a viscous solution can be created by simply mixing a small amount of hyaluronic acid.

[0039] (Durability evaluation of the fabricated substrate) First, we evaluate the substrate processing system used in this study, which involves modifying the substrate with GOPS and then applying a polysaccharide-mixed PEDOT:PSS solution to form a film. Contact angle measurements were performed on the GOPS-modified substrate and the substrate that had only been treated with hydrophilicity. Pure water was dropped onto the substrate and the average of five different points was used for discussion. The contact angles of the substrate that had only been treated with hydrophilicity and the substrate that had been treated with GOPS were 4.2° and 25.2°, respectively, and it was considered that the GOPS treatment on the substrate had progressed.

[0040] Based on the results of the viscosity measurements, the following ratios of polysaccharide and PEDOT:PSS in the solution to be spin-coated were selected: PEDOT:PSS only (neat), hyaluronic acid mixed solution hya1 / 48 (the notation 1 / 48 indicates that the mixed mass ratio of PEDOT:PSS:hyaluronic acid is 48:1), hya1 / 12 (the notation 1 / 12 indicates that the mixed mass ratio of PEDOT:PSS:hyaluronic acid is 412:1), chondroitin mixed solution cho1 / 48 (the notation 1 / 48 indicates that the mixed mass ratio of PEDOT:PSS:chondroitin is 48:1), cho1 / 12 (the notation 1 / 12 indicates that the mixed mass ratio of PEDOT:PSS:chondroitin is 12:1).

[0041] First, we will discuss the state of the substrates before and after immersion in pure water. In the crosslinker-added system, the entire film remained on all substrates even after overnight immersion. This confirmed that in the crosslinker-added system, a crosslinking reaction occurred due to GOPS, resulting in a water-resistant film. On the other hand, in the substrate modification system, only the hyaluronic acid mixed film remained entirely on the substrate, while the other films were observed to peel off from the substrate during immersion in pure water. Furthermore, the UV-vis absorption spectrum of the substrate-modified hyaluronic acid mixed film was measured immediately after spin coating and after immersion in pure water for 90 hours. The decrease rate of the PSS absorption peak was almost the same in the substrate-modified system compared to the cross-linking agent-added system, which means that there was almost no dissolution of the hyaluronic acid mixed film. From the above, it can be said that a stable membrane can be obtained in the crosslinking agent-added system. On the other hand, in the substrate modification system, a stable membrane can be produced when hyaluronic acid is mixed.

[0042] [Experimental Example 2] Each film was then applied to an organic electrochemical device. The OECT substrate was pre-cleaned by ultrasonic treatment in acetone (Nacalai Tesque), IPA (Kanto Chemical), and pure water for 15 minutes each. A glass substrate stored in IPA was vacuum-deposited with 6 nm of Ti and 60 nm of Au, and then rinsed with acetone, IPA, and pure water. The two treatments were performed in the same way as the substrate described above. As a substrate treatment system, a polysaccharide-mixed PEDOT:PSS solution was spin-coated onto a GOPS-treated substrate, and a polysaccharide-mixed PEDOT:PSS solution with GOPS added as a crosslinker (polysaccharide mixing ratio to PEDOT:PSS: hya1 / 48, hya1 / 12) was spin-coated onto a substrate that had only been hydrophilically treated. The substrate was then annealed at 130°C for 30 minutes to obtain a spin-coated film. The spin-coating conditions were 400 rpm for 10 seconds and 3000 rpm for 60 seconds. In the cross-linking agent-added system, after the substrate treatment described above, the substrate was spin-coated with a polysaccharide-mixed PEDOT:PSS solution (polysaccharide mixing ratios in PEDOT:PSS were hya1 / 48, hya1 / 12, and cho1 / 48), and the same procedure was followed. In addition, a film containing no hyaluronic acid or chondroitin was also prepared by spin-coating only the PSS solution (neat) onto the substrate in the cross-linking agent-added system, followed by the same procedure. The fabricated OECT device was analyzed using a 4155C semiconductor parameter analyzer (Keysight Technologies, Inc.) in a Faraday cage using phosphate buffered saline (PBS) as the electrolyte.

[0043] <Results and Discussion> First, to check whether the experimental conditions were appropriate, we performed measurements on an OECT made with a neat film (a PEDOT:PSS film with no polysaccharides added). The output curve showed the same depletion mode operation as known OECTs. The transfer curve also showed a similar trend to known OECTs. In addition, the transconductance values ​​of the OECT made with this and known PEDOT:PSS were normalized by the film thickness, channel length, and channel width (equation (3)), and the normalized transconductance g m * It was decided.

[0044]

number

[0045] Here, l is the channel length, w is the channel width, and d is the film thickness.

[0046] Table 1 shows a comparison of the results of this study with the values ​​of known OECTs (transconductance comparison).

[0047] [Table 1]

[0048] The fabricated OECT has a high current response, which is almost equal to that of a known OECT (best) and about five times that of an OECT (typical). This confirms that the fabrication procedures for the PEDOT:PSS solution and the OECT device in this experiment are appropriate.

[0049] Next, measurements were performed on the mixed films, and the output curves confirmed the depletion mode operation of the OECT in all devices, just as with the neat film. In addition, the transfer curves were also confirmed to be similar to those of the neat-film OECT. These results demonstrated that the OECT device was functioning normally.

[0050] FIG. 4 shows a box plot of the normalized maximum transconductance value of the electrodes on each substrate. The transconductance value of the PEDOT:PSS solution does not decrease significantly when polysaccharides are mixed, and it can be seen that different behavior is exhibited depending on the type of polysaccharide and the mixing ratio. Furthermore, when comparing hyaluronic acid mixed films, the transconductance value was higher in the substrate modified system than in the system with added crosslinker. It has been reported that the addition of GOPS reduces electrical conductivity, and this result can be said to solve that problem. Including the number of normally operating electrodes, the substrate modified hyaluronic acid 1 / 48 mixed film can be said to have the best performance of all the films created this time.

[0051] [Experimental Example 3] The drain voltage was set to -0.4V and the gate voltage to -0.2V, and the drain current was recorded approximately every 0.8 seconds. The OECT was operated with these settings and the current was allowed to stabilize. Then, glucose / PBS solution was gradually added to the PBS in which the gate was immersed, changing the glucose concentration in the gate electrolyte solution. After waiting 3-5 minutes, the drain current was read. From the measurement results, the glucose detection range and sensitivity of the fabricated device were calculated to evaluate the device's performance.

[0052] <Results and Discussion> (Glucose responsiveness evaluation) A glucose response experiment was carried out on the substrate modified hya1 / 48 film and the crosslinker added PEDOT:PSS film. The results are shown in Figure 5. In this experiment, the initial stabilization time was set to 6 minutes, and the interval for changing the glucose concentration was set to 3 minutes.

[0053] Based on the measured data, the glucose detection range and sensitivity of the device fabricated this time were calculated. The concentration was taken as a logarithm and plotted against the change in drain current. Figure 6 shows a semi-log plot of the glucose response experiment. The sensitivity was calculated by drawing a calibration curve and calculating the change in drain current when the glucose concentration changed by 10 mM.

[0054] The glucose detection range of the device created was 1-10mA (16μA / dec). For monitoring blood glucose levels in the human body, a measurement range of 4-8mM is sufficient, so the results show that this is a practical device. Table 2 also shows a comparison with previously reported non-enzymatic glucose sensors. The device created this time is extremely easy to fabricate compared to the other two, and can measure at the same range and sensitivity, so it is expected to be used as a new non-enzymatic glucose sensor.

[0055] [Table 2]

[0056] In this invention, the hya1 / 48 membrane modified with the substrate showed particularly good glucose detection characteristics. The reason why the substrate modified system is superior to the cross-linking agent added system is that when the cross-linking agent is added directly to the PEDOT:PSS solution containing polysaccharides, cross-linking proceeds rapidly and cross-links the polysaccharides together with the PEDOT:PSS, whereas in the substrate modified system, the cross-linking is slowed down by applying the PEDOT:PSS containing polysaccharides to the cross-linking agent modified on the substrate, and cross-linking occurs in a way that allows the effect of the polysaccharides to be expressed. On the other hand, the reason why hyaluronic acid has superior glucose detection properties to chondroitin sulfate is presumably because the highly acid-dissociable sulfo groups contained in chondroitin sulfate inhibit the above-mentioned cross-linking action and do not achieve sufficient cross-linking, whereas the interaction between the carboxyl groups in hyaluronic acid achieves a moderate cross-linking action and forms the desired cross-linked structure described above.

[0057] [Registered trademark] "Clevios" is a registered trademark of Heraeus Deutschland GmbH & Co. KG in Japan. [Industrial Applicability]

[0058] In the organic electrochemical device of the present invention, instead of the conventional PBA, a polysaccharide such as hyaluronic acid having a similar chemical structure to glucose is used as the glucose sensing site, and a conductive polymer film is produced by simply mixing this with a conductive polymer. In particular, a glucose response was observed in a glucose concentration range of 1 to 10 mM in a conductive polymer film made by mixing PEDOT:PSS and sodium hyaluronate (hya). This range falls within the range of general blood glucose levels. Therefore, the organic electrochemical device of the present invention is expected to be used not only as a blood glucose level monitor, but also as a taste sensor for fruit juice, beverages, etc. [Explanation of symbols]

[0059] 100 Organic Electrochemical Devices 102 Gate electrode 104 Channels 106 Source electrode 108 Drain electrode 110 Electrolytes 112 Insulating Substrate

Claims

1. A channel including a conductive polymer and a glycosaminoglycan, a source electrode, a drain electrode, and a gate electrode; the glycosaminoglycan is a glycosaminoglycan having a repeating structure of a disaccharide of N-acetylglucosamine and at least one sugar selected from the group consisting of glucuronic acid, iduronic acid, and galactose; the source electrode and the drain electrode are in contact with and electrically connected to the channel; If an electrolyte is present in contact with the gate electrode and the channel, the gate electrode can be electrically connected to the channel via the electrolyte, and the electrolyte is at least one selected from the group consisting of an electrolyte solution and an ionic liquid. Organic electrochemical devices.

2. 2. The organic electrochemical device of claim 1, wherein the conductive polymer is PEDOT:PSS.

3. The organic electrochemical device of claim 1 , wherein the glycosaminoglycan is hyaluronic acid.

4. The organic electrochemical device of claim 1 , wherein the electrolyte is a body fluid.

5. The organic electrochemical device of claim 4 , wherein the body fluid is blood.

6. The organic electrochemical device according to any one of claims 1 to 5, which is a glucose sensor.

7. 4. The organic electrochemical device according to claim 1, wherein the gate electrode is electrically connected to the channel via the electrolyte solution.

8. The organic electrochemical device of claim 7 which is an organic electrochemical transistor.

9. preparing a channel-forming composition comprising a conductive polymer and a glycosaminoglycan; The channel-forming composition is applied onto an insulating substrate on which a source electrode and a drain electrode are disposed, so that the channel-forming composition is in contact with the source electrode and the drain electrode to form a channel; disposing a gate electrode so as to be in electrical contact with the channel via an electrolyte; A method for manufacturing an organic electrochemical device, comprising the steps of: The glycosaminoglycan is a glycosaminoglycan having a repeating structure of a disaccharide of N-acetylglucosamine and at least one sugar selected from the group consisting of glucuronic acid, iduronic acid, and galactose. A method for manufacturing an organic electrochemical device.

10. The method for producing an organic electrochemical device according to claim 9 , wherein the gate electrode is disposed on the insulating substrate.